2023
DOI: 10.1111/famp.12851
|View full text |Cite
|
Sign up to set email alerts
|

Relational concerns and change in relationship satisfaction in a relationship education program

Abstract: Lower income couples tend to report more difficulty sustaining high-quality intimate relationships. As a result, policy initiatives have been enacted to fund relationship education (RE) programs that aim to increase lower income couples' relationship satisfaction. Generally, these programs demonstrate small, albeit statistically significant improvements in mean levels of relationship functioning. It is critical, however, to understand if RE programming influences the developmental course of intimate relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Our findings not only advance theoretical discussions regarding the contextual embeddedness of family processes but also have important implications for practitioners working with families in various cultural and subcultural groups. Empirical research has shown that family‐supportive programs can enhance romantic‐relationship satisfaction (Kanter et al, 2024), and evaluations of existing intervention programs based on diverse populations in the United States have consistently found that interventions targeting couples' relationships can benefit the development of couples' children (Pruett et al, 2017). In Chinese communities, intervention programs that aim to enhance child welfare perhaps should extend their efforts from parent–child dyads to interparental relations and should adopt emerging adapted or indigenized interventions for couples (Hsiao & Li, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings not only advance theoretical discussions regarding the contextual embeddedness of family processes but also have important implications for practitioners working with families in various cultural and subcultural groups. Empirical research has shown that family‐supportive programs can enhance romantic‐relationship satisfaction (Kanter et al, 2024), and evaluations of existing intervention programs based on diverse populations in the United States have consistently found that interventions targeting couples' relationships can benefit the development of couples' children (Pruett et al, 2017). In Chinese communities, intervention programs that aim to enhance child welfare perhaps should extend their efforts from parent–child dyads to interparental relations and should adopt emerging adapted or indigenized interventions for couples (Hsiao & Li, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…At study entrance and 30 months after couples enrolled in the SHM program, each partner responded to an item assessing their relationship satisfaction (“All things considered, how happy are you with your marriage”; 1 = completely unhappy to 7 = completely happy ). This item is sensitive in capturing changes in relationship functioning, associated with changes in individual functioning, and used in prior large‐scale evaluation studies (Kanter et al, 2023; Knopp et al, 2022; Lundquist et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Other recent studies have examined different trajectories of change among those receiving active CRE or a control condition. Using data from the Supporting Healthy Marriage trial of low-income couples, Kanter et al (2023) found that men in the intervention group relative to control group were more likely to belong to a group that maintained stable and high relationship satisfaction over time. Le et al (2023) examined low-income couples receiving one of two online relationship interventions compared to a waitlist control and found that men and women in the intervention condition were more likely to be in a group that achieved large improvement over time relative to the control group.…”
Section: The Prosaaf Interventionmentioning
confidence: 99%